Burst of the property bubble and Hong Kong's changing land and housing policies post-1997. Issue 2 (3rd March 2016) - Li, Si-ming
Abstract: Momentous events have characterized the Hong Kong Special Administrative Region since its founding in 1997. Among these were drastic and repeated changes in housing and policies, shifting from one emphasizing the role of the state to one purportedly relying primarily on market forces, and then back to a more proactive stance of the state. Associated with these changes were roller-coaster movements in residential prices and housing completions. These developments took place in the context of phenomenal upheavals within and beyond Hong Kong: the Asian financial crisis and the burst of Hong Kong's property bubble; the contestation of Hong Kong's autonomy under "one country, two systems"; and the flooding of "hot money" consequent upon repeated rounds of quantitative easing by the Federal Reserve of the United States to counteract the global financial crisis of 2007–2008 and the Great Recession that followed.